2014
DOI: 10.5863/1551-6776-19.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intravenous Magnesium Sulfate for the Treatment of an Acute Asthma Exacerbation in Pediatric Patients

Abstract: OBJECTIVES:The standard of care for treatment of an asthma exacerbation includes oxygen, inhaled shortacting bronchodilators, and systemic corticosteroids; adjunctive therapies, such as intravenous magnesium sulfate, can be used for patients who are having life-threatening exacerbations. The purpose of this study was to analyze the prescribing patterns as well as the safety of intravenous magnesium sulfate for the treatment of acute asthma exacerbations in pediatric patients across multiple hospitals in New Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 13 publications
0
27
0
2
Order By: Relevance
“…There were no cases of ‘clinical hypermagnesemia’ related to treatment overdosing (almost exclusively in patients with renal dysfunction). Therefore, MgSO 4 appears to present an optimal safety profile .…”
Section: Therapeutic Index and Cost‐effectivenessmentioning
confidence: 97%
See 1 more Smart Citation
“…There were no cases of ‘clinical hypermagnesemia’ related to treatment overdosing (almost exclusively in patients with renal dysfunction). Therefore, MgSO 4 appears to present an optimal safety profile .…”
Section: Therapeutic Index and Cost‐effectivenessmentioning
confidence: 97%
“…Tracheal intubation (IV) (31) 30 mgÁkg À1 Laryngospasm (IV) (23,33,34) 15 mgÁkg À1 Bronchospasm (IV) (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) 50-100 mgÁkg À1 + 40-50 mgÁkg À1 Áh À1 Bronchospasm (nebulized) (47)(48)(49)(50)(51)(52)(53)(54)(55) 40 mgÁkg À1 or 150 mg (total dose) Antiadrenergic response Cardiopulmonary bypass (IV) (57-60) 25-50 mgÁkg À1 Long QT syndrome (IV) (61) 30-50 mgÁkg À1 + 5-20 mgÁkg À1 Áh À1 Neonatal pulmonary hypertension (IV) (63) 200 mgÁkg À1 + 20-150 mgÁkg À1 Áh À1 Pheocromocytoma (IV) (64) 30-50 mgÁkg À1 + 5-20 mgÁkg À1 Áh À1 Organ protection Neuroprotection (IV) (68-72) 250 mgÁkg À1 Áday À1 Myocardial protection (cardioplegia) (73,74) 40-80 mgÁkg À1 Hypomagnesemia Perioperative hypomagnesemia (IV) (58,59) 25-50 mgÁkg À1 AE 5-20 mgÁkg À1 Áh À1 alveolar concentration by 50% and the induction dose of propofol; it shortens the latency time until a bispectral index value <60 is reached; and it reduces ventilation requirements (tidal volume and respiratory rate) as metabolism decreases (O 2 consumption and CO 2 production) (2,6). Sevoflurane has certain excitatory effects on the central nervous system, which may be associated with increased seizure activity in children.…”
Section: Muscle Relaxationmentioning
confidence: 99%
“…It acts by decreasing intracellular calcium by blocking its entry and release from the endoplasmic reticulum and by activating the sodiumcalcium pumps. A number of studies support the safety of intravenous magnesium as an adjuvant therapy [33,34]; these studies did not include non-ICU inpatient floors. In the emergency room setting, a systematic review and subsequent randomized controlled trial of inhaled magnesium for enhanced bronchodilation demonstrated limited efficacy [35,36], while two metaanalyses have demonstrated more consistent effect of intravenous magnesium in preventing hospital admission [37,38].…”
Section: Magnesium Sulfatementioning
confidence: 99%
“…A single dose of intravenous magnesium sulphate has been shown to be safe and effective in adults and children with acute severe asthma, who have had a poor response to initial therapy 7 . It is a safe drug to administer, but there have been minor side effects reported, such as epigastric or facial warmth, flushing, pain and numbness at the infusion site, dry mouth, malaise, and hypotension 8 . In some cases, severe hypotension may develop.…”
Section: Introductionmentioning
confidence: 99%